2021
DOI: 10.3389/fpsyt.2021.679206
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Expression of Plasma miRNA-320a and let-7b-5p in Heroin-Dependent Patients and Its Clinical Significance

Abstract: Heroin use disorder is a chronic and relapsing disease that induces persistent changes in the brain. The diagnoses of heroin use disorders are mainly based on subjective reports and no valid biomarkers available. Recent researches have revealed that circulating miRNAs are useful non-invasive biomarkers for diagnosing brain diseases such as Alzheimer's disease, multiple sclerosis, schizophrenia, and bipolar disorder. However, studies on circulating miRNAs for the diagnosis of heroin use disorders are rarely rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Based on the above studies, we speculated that the dysfunction of miR-320 in plasma and exosomes could reflect the corresponding dysfunction in the brain caused by MA addiction. Previously, our group have found that the levels of miR-181a, miR-320a, and let-7b-5p in circulating plasma significantly increased in heroin-dependent patients, and demonstrated that these miRNAs can distinguish heroin addicts from healthy controls (22,33). Tobacco affects the central and circulating expression of miRNAs and is prevalent in drug-addicted patients (21,34).…”
Section: Discussionmentioning
confidence: 98%
“…Based on the above studies, we speculated that the dysfunction of miR-320 in plasma and exosomes could reflect the corresponding dysfunction in the brain caused by MA addiction. Previously, our group have found that the levels of miR-181a, miR-320a, and let-7b-5p in circulating plasma significantly increased in heroin-dependent patients, and demonstrated that these miRNAs can distinguish heroin addicts from healthy controls (22,33). Tobacco affects the central and circulating expression of miRNAs and is prevalent in drug-addicted patients (21,34).…”
Section: Discussionmentioning
confidence: 98%
“…Also, Dakterzada aimed to find miRNAs in plasma from AD participants, identifying a BACE-1 related panel of biomarkers different from the miRNAs in the present work 33 . It could be due to the use of a different identification technique based on microarrays analysis 34 . The different methodologies employed could affect the miRNAs selection, so it should be taken into account in comparisons with other studies 33 .…”
Section: Discussionmentioning
confidence: 99%
“…We identified 26 microRNAs that are predicted to bind at least three heroin-associated circRNAs and an additional 12 microRNAs predicted to bind circGrin2b, circAdcy5, circAnks1a, circSlc24a2 or circUbe2cbp. Of these, let-7b-5p, which is predicted to bind circAdcy5, has been reported to be elevated in both the serum and the plasma of patients with heroin-use disorder [52,53]. Moreover, the putative targets of the heroinassociated circRNA-miRNA network include genes that have been studied extensively in the field of addiction, including Bax, Egr1, Elk1, Mapk3 (Erk1) and Ncam1.…”
Section: Discussionmentioning
confidence: 99%